Pengaruh interval dan lama perendaman terhadap pertumbuhan dan pendewasaan embrio somatik tanaman sagu (Metroxylon sagu Rottb.) Effect of immersion interval and duration on the growth and maturation of somatic embryos of sago palm ( Metroxylon sagu Rottb.) - Imron RIYADI; . SUMARYON (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2009)
AbstractLiquid culture via temporary immersionsystem (TIS) has a potency for enhancingmaturity and uniformity of plant somatic embryos(SE). An experiment was conducted to determinethe effect of medium immersion interval andduration on the growth and maturation of sagoSE in TIS. A clump of SE at globular stagederived from sucker’s tip meristem culture wasused as material source. The SE were cultured ona modified Murashige and Skoog medium addedwith 0.01 mg/L ABA, 1.0 mg/L kinetin and0.1 mg/L GA 3 . The treatments used were TISwith immersion interval of 3, 6 and 12 hourswith duration of 1 and 3 minutes. Solid mediumwas used as a control. The results show that TISwith immersion interval 12 hours for threeminutes produced the highest SE biomass(14.6 g/flask) which had increased by 9.8-foldwithin six weeks. The longer of immersioninterval (less frequent) and the longer ofimmersion duration (three minutes) increasedsignificantly biomass fresh weight of of sago SE.SE biomass of sago on solid medium wassignificantly lower than those of in liquid mediaof TIS. The highest number of advanced stageembryos (torpedo, cotyledonary and earlygerminant) of 643 or 48.2% from the totalnumber of SE was achieved in TIS with 12 hoursinterval for three minutes. During the maturationof sago SE, the color of embryos has changedfrom mostly yellowish to greenish and reddish.AbstrakKultur cair dengan sistem perendaman sesaat(SPS) berpotensi untuk meningkatkanpendewasaan dan keseragaman embrio somatik(ES) tanaman. Penelitian ini bertujuan untukmenentukan pengaruh interval dan lamaperendaman terhadap proses pendewasaan ESsagu dalam SPS. Bahan yang digunakan berupaES fase globuler asal kultur pucuk tunas anakansagu. ES sagu dikulturkan dalam mediumMurashige dan Skoog yang dimodifikasiditambah ABA 0,01 mg/L; kinetin 1 mg/L danGA 3 0,1 mg/L. Perlakuan yang digunakan adalahkultur SPS dengan interval perendaman 3, 6 dan12 jam dengan lama perendaman 1 dan 3 menitserta kultur padat sebagai pembanding. Hasilpenelitian menunjukkan bahwa perlakuan SPSdengan interval perendaman 12 jam selama tigamenit menghasilkan bobot biomassa ES tertinggiyaitu 14,6 g/bejana yang meningkat 9,8 kalidalam waktu enam minggu. Interval peren-daman lebih lama (lebih jarang) dan lama peren-daman lebih panjang (tiga menit) meningkatkansecara nyata bobot segar biomassa ES sagu.Biomassa ES sagu pada medium padat secaranyata lebih rendah dibandingkan dengan kulturkotiledon dan kecambah dini) tertinggi yaitu 643atau 48,2% dari jumlah total ES diperoleh pada perlakuan SPS interval 12 jam dengan lama tigamenit. Seiring dengan pendewasaan ES sagu, terjadi perubahan warna dari sebagian besar kuning menjadi hijau dan merah.